A COMPARATIVE STUDY OF IMPACT OF DIGITIZATION IN TAXATION BETWEEN INDIA AND BANGLADESH - Dr. Nagesh Chandraiya Senigarapu, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
India as a developing country is committed to increasing tax revenue and achieving fiscal discipline with a view to increasing self-reliance. The external environment influencing the tax performance of India has changed remarkably as the country more and more integrated with the global economy during the 1990s. In recent years, the Government of India has initiated some administrative and policy reforms in the tax system. An improved tax administration in association with some pragmatic policy initiatives has of late resulted in a modest improvement in the tax to GDP ratio. However, the performance is still unsatisfactory as compared to other countries at a similar stage of economic development.